A comparative study of antenatal depression among urban and rural pregnant women in Gimbi District, Oromia, Ethiopia - Chala, Solomon; Desalegn, Markos; Oljira, Rut; Fite, Meseret Belete; Mecha, Sagni Hambisa; Hunde, Gemechis Megnaka (Frontiers in Public Health, 2024)
Background: Antenatal depression is a form of clinical depression that can be caused by stress and worries that can bring pregnancy to more severe levels. It has negative impacts on women, the family, and the community at large. The comparative study of antenatal depression among rural and urban pregnant women was less studied in Ethiopia and in this study area in particular.Objective: To compare the prevalence of antenatal depression and its associated factors among pregnant women in Gimbi Rural and Gimbi Urban residents, Ethiopia, 2023 Methods: A Community-based comparative cross-sectional study design was employed from February 1 to March 30, 2023. Systematic random sampling was used to select study participants. Data were collected using pretested interviewer-administered structured questionnaires. Binary logistic regression analysis was used to identify factors associated with antenatal depression. Variables having 0.25 and less p-value in the bi-variable logistic regression model were candidates for a multi-variable logistic regression model. Results: The prevalence of antenatal depression was 56(21.5%), [95% CI: [ 16.9-25.5]) among rural and 50 (19.2 %,) [95%] CI: [14.6-23.8]) among urban. Complications during pregnancy(AOR: 4.92, 95 % (CI: 1.35, 17.88), ever had depression (AOR:3.20, 95%(CI: 1.30, 7.85), drinking alcohol (AOR:3.78, 95% (CI: 1.24, 11.49), educational status (can read and write) (AOR:2.14, 95% (CI:1.05, 4.67) were associated factors to antenatal depression among urban mothers while, No antenatal care follow up (AOR:6.6, 95% (CI: 2.63, 16.85), unplanned pregnancy (AOR:4.51, 95%(CI:1.10, 1.86), complication during pregnancy (AOR:2.77, 95 % (CI: 1.30, 5.92) were associated factors with antenatal depression among rural mothers.The prevalence of antenatal depression in rural was higher than the prevalence of antenatal depression among urban mothers in the Gimbi district. Having complications during pregnancy, ever had depression, drinking alcohol, and educational status among urban mothers; complications during pregnancy, unplanned pregnancy, and No ANC follow-up were associated factors with antenatal depression among rural mothers. Therefore, quality family planning and ANC services should be provided for the women to reduce unplanned pregnancies and experience complication-free pregnancy periods respectively.